DESIGN, FORMULATION, AND CHARACTERIZATION OF STEARIC ACID-BASED SOLID LIPID NANOPARTICLES OF CANDESARTAN CILEXETIL TO AUGMENT ITS ORAL BIOAVAILABILITY - Mahajan, Anu; Kaur, Satvinder; Kaur, Satvinder (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Poor aqueous solubility and suboptimal oral bioavailability hamper the therapeutic efficacy of candesartan cilexetil (CDC). This study is designed to prepare solid lipid nanoparticle (SLN) of CDC and to enhance the oral absorption of CDC compared with free drug suspension. Methods: The development and characterization of CDC-loaded SLN, using stearic acid as main encapsulating lipid, stabilized with poloxamer188 using modified emulsification-ultrasonication technique.â€ Results: CDC-SLN with a total drug content of 88.33Â±1.23% and entrapment efficiency of 78.28Â±1.91%, with an average particle size of 197.9 nm and zeta potential value âˆ’21.3 mV, was prepared. Differential scanning calorimetry and powder X-ray diffraction (PXRD) results confirmed the molecular encapsulation of the drug in amorphous state. CDC-SLN released 60.43% of drug in comparison to 17.11% released by CDC suspension in 24 h (p<0.05). The results of pharmacokinetic studies in rat showed that AUC0âˆ’t of CDC-SLN was significantly enhanced over 3-folds than that of free drug suspension (p<0.05). Conclusion: SLN of CDC could be successful in improving the oral bioavailability of poorly soluble CDC.